Panocam: Combining panoramic video with acoustic beamforming for videoconferencing - Green, David; Fiala, Mark (Canadian Acoustics, 2004)
A panoramic audio/video sensor used for videoconferencing applications is discussed. A panoramic video camera combined with microphone array when placed at the center of a meeting table is found to be efficient in real time detection and tracking of the talkers seated around the table. The microphone beamformer is used to determine the instantaneous direction to the current talker. The potential talker is identified by detecting the motion automatically and is imaged by the panoramic video system.